Behavior of The RC Slab-Beam System Using Self Compacting Concrete - A. Alwash, Nameer; H. Naser Al-Mamoori, Fatimah (International Journal of Engineering and Technology, 2018)
The present study includes an experimental investigation of the behavior of square reinforced concrete slabs. These slabs are with and without edge beams under uniformly distributed load with corner supports using two types of self compacting concrete (SCC), the first type of SCC incorporated limestone filler and the other was without filler, the results obtained are compared with those obtained from conventional concrete (CC).The experimental program consists of testing nine square slab samples. Three of these slab samples are flat in shape with panel dimensions of 1050Ã—1050Ã—50 mm depth. The others three slab samples are of the same outer dimensions with surrounding edge beams of depth to slab thickness equal 100/50 and 100 mm width. The last three slab samples are similar to the former slab-beam systems but with increasing the depth of edge beams by 50%.In general, for a specified flat plate panel, the ultimate load carrying capacity can be increased, if the panel is restricted by four surrounding beams. The slab-beam samples with surrounding beams of depth to slab thickness equal to 3 showed greater ultimate load capacity by about 79.37%, 52% and 97.82% when compared with the corresponding flat slabs samples produced using CC, SCC with and without filler, respectively.Â Â